Closing Pakistan’s epilepsy treatment gap: The promise of home-based care - Nabeel Qaiser, Isbah; Bano, Haniya; Rafique, Muhammad Umar (Journal of the Pakistan Medical Association, 2026)
Epilepsy is very common in Pakistan, affecting more than 2 million people, with a higher prevalence in children (14.6 per 1000). [1] The challenge with epilepsy is the treatment gap, which refers to the difference between the number of people who need medical treatment for their condition and those who actually receive it. It is more than 80% due to social, cultural and financial constraints. This is due to inappropriate treatment-seeking behaviour and less prioritisation of the disease in the country. Furthermore, the stigmatisation of the disease is mostly seen in urban communities due to fear of repulsion, being ridiculed by society, job losses and increased dependency.[1][2] Children with this disease have decreased self-esteem and are more likely to drop out of school due to parental overprotection and denial of the disease.[1] Moreover, superstitious beliefs are accountable for making the disease such a taboo one. Therefore, innovative solutions are necessary to bridge the treatment gap. Home care delivery by trained primary care workers is a promising approach which can effectively reduce these challenges by providing accessible and consistent care in familiar environments. In a community-based, cluster-randomised trial, home-based provision for epilepsy was compared to routine care in a hospital-based clinic. After 10 months, there were overall fewer seizures in home-based health care compared to clinic care (P=0.002), The former group also showed greater adherence to anti-seizure medication(P=0.001) and were found less likely to drop out of this trial (P=0.003). The time to first seizure, adverse effects and personal impacts of seizure were the same in both groups. Furthermore, the ancillary analysis revealed that there were 20 unplanned or emergency visits to the hospital by home care recipients compared to 47 in clinic-based care.[3] Therefore, this trial’s findings are highly relevant to Pakistan, where epilepsy remains a critical yet neglected public health issue. This research demonstrates home-based care is a credible option, therefore, individuals with epilepsy should be empowered to manage their condition by adhering to medication rather than seeking hospital enrollment, which can be costly and isolating. The substantial reduction in the secondary treatment gap strongly supports home-based care. Moreover, treatment gap can be addressed by training healthcare professionals on epilepsy, identifying prevention strategies, and dispelling stigma.[4] Community awareness must be raised through media, campaigns, and home provision of anti-seizure medications.3 Support groups should be encouraged for people with epilepsy to share experiences and receive guidance.[1] These efforts can ultimately improve the lives of thousands living with epilepsy.